Histopathological findings in Dalmatian pelicans (Pelecanus crispus) naturally infected with avian influenza subtype A H5N1 in Bulgaria - STOIMENOV, G. M.; GOUJGOULOVA, G. V.; NIKOLOV, B.; PETROVA, R.; TENEVA, A.; DIMITROVA, I. (Journal of the Hellenic Veterinary Medical Society, 2018)
The aim of this study is to estimate the histopathological changes in visceral organs of naturally infected with the avian influenza virus (AIV) subtype A H5N1 dalmatian pelicans in Bulgaria. The identified gross lesions are: haemorrhagic small intestine, sparse content in gizzard and proventriculus, well defined hyperemia of the tracheal mucosa associated with petechiae, as well as meningeal and brain congestion. The infected birds exhibited the following histopathological changes: edema of the tracheal mucosa with loss of mucosal glands, mild to moderate congestion with focal necrosis and multifocal non suppurative encephalitis and gliosis, mononuclear infiltration in the cecum, and diffuse mononuclear infiltration in the submucosa of the small intestine. The virus was detected by virus isolation (VI) and RT-PCR from tissue samples (lung, trachea, small intestine, brain, proventriculus, cloaca) from the infected birds.